Suppression of Esophageal Cancer Stem-like Cells by SNX-2112 Is Enhanced by STAT3 Silencing - Xu, Dan-dan; Chen, Su-hong; Zhou, Peng-jun; Wang, Ying; Zhao, Zhen-dong; Wang, Xia; Huang, Hui-qing; Xue, Xue; Liu, Qiu-ying; Wang, Yi-fei; Zhang, Rong (Frontiers in Pharmacology, 2020)
Many studies have demonstrated that cancer stem cells (CSCs) or tumor-initiating cells (TICs) are responsible for tumor cell proliferation, chemotherapy resistance, metastasis, and relapse in various cancers. We, and others, have previously shown that the signal transducer and activator of transcription 3 (STAT3) signaling pathway is responsible for CSCs and TICs growth. Recent reports have indicated that the heat shock protein 90 (Hsp90) is also essential for the survival of CSCs and TICs. SNX-2112 is an Hsp90 inhibitor. However, it remains unclear whether proliferation of esophageal cancer stem-like cells (ECSLCs) is suppressed by SNX-2112 with knockdown of STAT3 (shSTAT3). Here, we explored the association between SNX-2112 with shSTAT3 and the suppression of ECSLCs growth. We found that the expression level of both STAT3 and p-STAT3 was higher in clinical esophageal cancer tissue than in the adjacent normal tissue, using western blot and qPCR analysis. Furthermore, differential expression analysis demonstrated that STAT3 was overexpressed in clinical specimens. We demonstrated that SNX-2112 inhibited cancer cell proliferation, decreased ABCB1 and ABCG2 gene expression levels and reduced the colony formation capacity of ECSLCs, which was enhanced by STAT3 silencing. Flow cytometry analysis revealed that the combination of SNX-2112 and shSTAT3 significantly induced apoptosis and cell cycle arrest at G2/M phase in ECSLCs. Levels of proliferation pathway proteins, including p38, c-Jun N-terminal kinase (JNK), and extracellular signal–regulated kinase (ERK) which were also client proteins of Hsp90, were also reduced. In addition, SNX-2112 with shSTAT3 inhibited the proliferation of ECSLCs in vivo. Finally, STAT3 overexpression eliminated the apoptotic and antiproliferative effects of SNX-2112 on ECSLCs. Hence, these results provide a rationale for the therapeutic potential of the combination of SNX-2112 with shSTAT3 in esophageal cancer, and may indicate new targets for clinical intervention in human cancer.